Pengaruh Pengalaman, Motivasi, Pendidikan terhadap Kinerja Karyawan PNS RSJD - Florencia Angelica; RR Niken Purbasari (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This study aims to identify and analyze the influence of work experience, work motivation, and educational background on employee performance at the Bangka Belitung Islands Provincial Hospital. The simple random sampling technique was used with a total sample of 136 respondents of civil servant employees. Data was collected by distributing questionnaires using a 5-point Likert scale to measure 24 statement items. They were using multiple regression analysis to determine the effect of all dependent variables on independent variables. The results showed that work motivation and educational background had an influence on employee performance, but work experience variables did not have an impact on the performance of employees of the Bangka Belitung Islands Provincial Hospital.